The impact of price promotions on confectionery and snacks on the energy content of shopping baskets: A randomised controlled trial in an experimental online supermarket - Luick, M; Pechey, R; Harmer, G; Bandy, L; Jebb, SA; Piernas, C (Elsevier, 2023)
Overconsumption of foods high in fat, sugars, and salt (HFSS) poses a significant risk to health. The government in England has passed legislation that would limit some price promotions of HFSS foods within supermarkets, but evidence regarding likely impacts of these policies, especially in online settings, is limited. This study aimed to determine whether there were any differences in the energy and nutrient content of shopping baskets after removing promotions on HFSS foods in an online experimental supermarket. UK adults (n = 511) were asked to select food from four categories with a £10 budget in an online experimental supermarket: confectionery; biscuits and crackers; crisps, nuts and snacking fruit; cakes and tarts. They were randomly allocated to one of two trial arms: (1) promotions present (matched to promotion frequency seen in a major UK retailer) (n = 257), or (2) all promotions removed from all products within the target food categories (n = 254). The primary outcome analysis used linear regression to compare total energy (kcal) of items placed in shopping baskets when promotions were present vs. absent, while secondary analyses investigated differences in nutrients and energy purchased from individual food categories. Mean energy in food selected without promotions was 5156 kcal per basket (SD 1620), compared to 5536 kcal (SD 1819) with promotions, a difference of −552kcal (95%CIs: −866, −238), equivalent to 10%. There were no significant differences in energy purchased for any individual category between groups. No evidence was found of other changes in nutritional composition of baskets or of significant interactions between the impact of promotions and participant characteristics (gender, age, ethnicity) on energy purchased. Removing promotions on HFSS foods resulted in significantly less total energy selected in an online experimental supermarket study.